Instagram Reels in Local Government Tourism Promotion: An Analysis of @disparbudgarut's Digital Content Strategy - Ganjar Wibowo; Manik Sunuantari; Imsar Gunawan; Winner Riyawan (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2026)
This study reviews the performance of Instagram Reels as a tourism communication tool used by local governments, focusing on @disparbudgarut accounts as an example of cases. This study aims to analyze the performance of Instagram Reels as a tourism communication medium, identify the characteristics of high-performance Reels content, and examine its contribution in supporting local government tourism communication and promotion. This research uses a descriptive qualitative approach, supported by digital analysis through the NotJustAnalytics platform, SocialBlade, and visual evaluation of content. The findings show that Reels is the most effective content format, with a view rate of 96.67%, much better than other official photo or video content. Reels are able to show a natural, authentic, and aesthetic visual appearance, as well as convey an interesting short story about the atmosphere of Garut, the activities of the local community, and its natural beauty. This phenomenon supports the theory of Uses and Gratifications, which explains that audiences watch content because it meets the needs of entertainment, information, identity, and social engagement. Reels also contribute greatly to shaping the image of tourist destinations, as they are in accordance with Instagram's algorithm and are in harmony with the visual tastes of the digital generation. However, the local government's content strategy is still inconsistent, with the dominance of bureaucratic content that is less in demand by the public. Based on the results of the research, it is recommended to implement a data-based content strategy, build a creative team, standardize visual design, and work with local creator communities so that the potential of Reels in tourism promotion can be maximized. This study has an important role in shaping local government communication policies in the midst of the development of the digital era. Keywords: Social Media Analytics; Digital Branding; Instagram Reels; Communication of Local Governments; Tourism Promotion.